Erythrokeratolysis hiemalis: scaling erythematous genodermatosis with seasonal manifestation - Krahl, Dieter; Sigwart, Andrea; Hartschuh, Wolfgang; Anton-Lamprecht, Ingrun; Petzoldt, Detlef (Der Hautarzt, 1994)
Erythrokeratolysis hiemalis, keratolytic winter erythema or Oudtshoorn skin has been reported from the South African district of Oudtshoorn as a dominantly inherited dermatosis beginning in early childhood, in some cases with circinar scaling erythemas. Seasonal manifestation in winter-time and a characteristic multiform histology distinguish this dermatosis from other childhood scaling erythemas. We present clinical, histological and preliminary immunohistological data of a 4-year-old girl with the attributes of erythrokeratolysis hiemalis. No ancestors from the endemic region were traced. The lack of further cases in the family is interpreted as indicative of a spontaneous dominant new mutation.
Gesehen am 04.10.2023